A Wake-up Call for Burnout in Portuguese Physicians During the COVID-19 Outbreak: National Survey Study - Ferreira, Sónia; Sousa, Mafalda Machado; Moreira, Pedro Silva; Sousa, Nuno; Picó-Pérez, Maria; Morgado, Pedro (JMIR Publications, 2021)
BackgroundThe COVID-19 outbreak has imposed physical and psychological pressure on health care professionals, including frontline physicians. Hence, evaluating the mental health status of physicians during the current pandemic is important to define future preventive guidelines among health care stakeholders. ObjectiveIn this study, we intended to study alterations in the mental health status of Portuguese physicians working at the frontline during the COVID-19 pandemic and potential sociodemographic factors influencing their mental health status. MethodsA nationwide survey was conducted during May 4-25, 2020, to infer differences in mental health status (depression, anxiety, stress, and obsessive compulsive symptoms) between Portuguese physicians working at the frontline during the COVID-19 pandemic and other nonfrontline physicians. A representative sample of 420 participants stratified by age, sex, and the geographic region was analyzed (200 frontline and 220 nonfrontline participants). Moreover, we explored the influence of several sociodemographic factors on mental health variables including age, sex, living conditions, and household composition. ResultsOur results show that being female (β=1.1; t=2.5; P=.01) and working at the frontline (β=1.4; t=2.9; P=.004) are potential risk factors for stress. In contrast, having a house with green space was a potentially beneficial factor for stress (β=-1.5; t=-2.5; P=.01) and anxiety (β=-1.1; t=-2.4; P=.02). ConclusionsIt is important to apply protective mental health measures for physicians to avoid the long-term effects of stress, such as burnout.